Citizen Complaint System for Urban Maintenance Using GIS - Mohd Sohel, Deshmukh; Kale, KV (International Journal of Computer Sciences and Engineering, 2025)
In today’s time the working of local government body is very important and to meet the requirement of the digitized society the local body also need to improve their working style. some of the responsibility of the local government body is to take care of the wear and tear in the city and to keep the city clean, As many of the cities in India are not fully digitized or aren’t smart cities yet where sensor and camera would find out the faults the cities are mostly depended on the citizen input as complaints for this work, But the current method for complaining is very tedious and time consuming, so most of the people just ignore the problem and try to live with it, so change this we have come up with online complaint system in which people can easily lodge their complaints from their phone instead of going to the respective office, they can also look what is the current status is of their complaints and what actions are been taken by the local government body, all they need to do is just take a picture of the problem and submit it to the local government body for actions with the details of the problem, So by this we can evolve from being a normal city to smart city in steps.